Geographical variation and predictors of physical activity level in adults with congenital heart disease. (March 2019) - Larsson, Lena; Johansson, Bengt; Sandberg, Camilla; Apers, Silke; Kovacs, Adrienne H.; Luyckx, Koen; Thomet, Corina; Budts, Werner; Enomoto, Junko; Sluman, Maayke A.; Wang, Jou-Kou; Jackson, Jamie L.; et al.
Abstract: Background: Physical activity is important to maintain and promote health. This is of particular interest in patients with congenital heart disease (CHD) where acquired heart disease should be prevented. The World Health Organization (WHO) recommends a minimum of 2.5 h/week of physical activity exceeding 3 metabolic equivalents (METS) to achieve positive health effects. It is unknown whether physical activity levels (PAL) in adult CHD patients differ by country of origin. Methods: 3896 adults with CHD recruited from 15 countries over 5 continents completed self-reported instruments, including the Health Behaviour Scale (HBS-CHD), within the APPROACH-IS project. For each patient, we calculated whether WHO recommendations were achieved or not. Associated factors were investigated using Generalized Linear Mixed Models. Results: On average, 31% reached the WHO recommendations but with a great variation between geographical areas (India: 10%–Norway: 53%). Predictors for physical activity level in line with the WHO recommendations, with country of residence as random effect, were male sex (OR 1.78, 95%CI 1.52–2.08), NYHA-class I (OR 3.10, 95%CI 1.71–5.62) and less complex disease (OR 1.46, 95%CI 1.16–1.83). In contrast, older age (OR 0.97, 95%CI 0.96–0.98), lower educational level (OR 0.41, 95%CI 0.26–0.64) and being unemployed (OR 0.57, 95%CI 0.42–0.77) were negatively associated with reaching WHO recommendations. Conclusions: A significant proportion of patients with CHD did not reach the WHO physical activity recommendations. There was a large variation in physical activity level by country of origin. Based on identified predictors, vulnerable patients may be identified and offered specific behavioral interventions.